Study of the reform of teaching the course “Principles of Economics” based on the OBE concept - Han C. (Modern science and education: choosing the future, 2024)
The article suggests that as part of the global transformation of the higher education industry, there is a gradual transition from the use of traditional teaching methods to student-centered teaching strategies focused on achieving educational outcomes. These principles are implemented within the framework of the OBE concept. The purpose of the study is to analyze the possibilities and methodology for reforming the “Principles of Economics” curriculum based on the OBE concept. It is shown that within the framework of the concept, teachers should clearly focus on developing in students the competencies they need 5 years after graduation. The conceptual core of EBE consists of such key advantages as clarity of goal setting, flexibility of methodological tools, the possibility of comparative analysis of educational achievements and involvement of subjects of the educational process. OVE creates conditions for comparing educational achievements both at the individual and institutional l
Keywords: экономическая грамотность; методика преподавания; Teaching Methods; принципы экономики; экономическая культура; реформа преподавания; economic culture; economic literacy; principles of economics; teaching reform; concept of OBE; концепция ОВЕ